Form and content of Jamaican cannabis edibles - Carole M. Lindsay; Wendel D. Abel; Erica E. Jones-Edwards; Paul D. Brown; Khalia K. Bernard; Tainia T. Taylor (BMC, 2021)
Abstract Background In 2017, the Jamaican government banned the sale of cannabis-infused edibles after reports of over-intoxication in adults and children. There is a general lack of public awareness regarding the risk involved with edible dosage. Vandrey et al. in 2015 reported that random cannabis edibles sampled from dispensaries in California and Washington in the USA failed to meet the basic labeling standards for pharmaceuticals (Vandrey et al.; JAMA 2015). This study aims to measure the levels of THC and CBD in a variety of edibles available locally in order to establish current cannabinoid content and to report on safety and packaging. This study is deemed necessary as no such study has been done to measure the potency levels of edibles and to raise awareness of the potential risk to children. Methods Forty-five cannabis-infused edible items were collected as convenience samples over a 4-year period (2014-2018) and analyzed. The QuEChERS technique (modified) was used to extract cannabinoids from each item. The extracts were then derivatized with MSTFA prior to analysis by gas chromatography-mass spectrometry (GC-MS). The descriptive statistics were calculated using the Statistical Package for Social Sciences-SPSS Software. Descriptive statistics presented include the mean, median, standard deviation, and range for each product category. The distribution of data with a box and whisker plot and frequency of THC to CBD ratios with a histogram was also presented. Results Edibles on the Jamaican market comprise baked goods, candies, frozen foods, and beverages. Eighty-six percent of samples were poorly labeled and failed to meet basic labeling requirements. None of the packages were observed to be child-proof. THC levels ranged from 0.01 to 99.9 mg per product while CBD levels ranged from 0.001 to 69.2 mg per product. The highest THC and CBD levels were detected in cookies and brownies. Thirty percent of the samples had THC levels greater than the recommended 10 mg THC per serving. Conclusion The lack of proper labeling and the wide range of THC levels in cannabis edibles raises public health concerns for all consumers including inexperienced persons who may be at a greater risk of overdosing. Concern must also be raised over the possibility that the attractive and tasty ways in which the drug is being presented might tempt young children and teens to take cannabis. Impact statement It is hoped that this information will raise public awareness of the current potential danger these edibles pose to children and inexperienced users and that policymakers will see the need for the imposition of suitable regulations.